The Effect of Digital Project-Based Learning and Self-Confidence on Students’ Arabic Learning Achievement - Nurjanna; M.Yusuf T; Rappe; Haniah (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study examines the correlation between digital project-based learning and self-confidence on Arabic language learning achievement. Employing a 2 × 2 treatment-by-level research design, the implementation of digital project-based learning demonstrated a positive effect on student learning outcomes. This can be seen in the score differences between classes that applied digital project-based learning and those that used project-based learning without digital assistance. The average score of the experimental class was 60.31, while the control class achieved an average score of 35.69. This finding was supported by the results of a two-way ANOVA, which showed a significance value of 0.000 < 0.05, indicating a significant difference in Arabic learning achievement between students taught using digital project-based learning and those taught without digital assistance. Similarly, self-confidence also showed a positive effect on Arabic learning achievement. Students with high self-confidence achieved higher scores than those with low self-confidence, with average scores of 63.85 and 32.15, respectively. This result was further supported by the two-way ANOVA test, which yielded a significance value of 0.000 < 0.05, indicating a significant difference in Arabic learning achievement between students with high and low self-confidence.